The Effect of Fine Bubbles Application and LED Irradiation on Damage and Chlorophyll Content of Cut Romaine Lettuce - Ciptaningtyas, Drupadi; Nur Adhillah, Syahla; Hasta Pratopo, Lukito; Thoriq, Ahmad (Universitas Brawijaya, 2024)
The current change in society’s lifestyle reflects a tendency towards a more practical life, including food consumption. Romaine lettuce is one of the minimally processed vegetables sold in ready-to-eat packaging and is a common component in salads. However, minimal processing makes romaine lettuce more susceptible to deterioration and a decrease in chlorophyll content. Efforts was made to reduce damage and decrease chlorophyll content in romaine lettuce through fine bubbles application and blue and white LED irradiation. In this study, cut romaine lettuce was washed using fine bubbles and irradiated with blue and white LEDs with various exposure times. The results showed that fine bubbles increased dissolved oxygen and their application in washing cut romaine lettuce reduced surface damage by 20.55%. Chlorophyll content was tested by extracting the lettuce in ethanol solvent and measuring its absorbance using a UV-Vis spectrophotometer. The chlorophyll content test results showed that, after irradiation and six days of storage, the romaine lettuce did not show an increase in chlorophyll content. This indicates that while fine bubble washing can reduce surface damage, blue and white LED irradiation has not been able to maintain or increase chlorophyll content, as the chlorophyll degraded during the storage period.